LEGITIMASI KEPEMIMPINAN BANI QURAISY - Setiadi, Ozi; Amiruddin, Muh (RIWAYAH, 2019)
The leadership of the Banu Quraish received special attention from the Prophet Muhammad. This attention is poured in many traditions narrated by narrators of traditions. Imam Ahmad, Imam Bukhari, and Imam Muslim are scholars who also narrated the hadith. This also received the attention of Islamic thinkers. Al-Farabi, Ibn Thaimiyyah, Al Farabi and Nashiruddin Thusi have different opinions. In general it can be concluded from the opinion of the scholars of hadith and Islamic thinkers that; First, there is no textual debate about the leadership of the Banu Quraish and Islamic thinkers accept this. Second, the Banu Quraysh became the sunatullah provisions, became leaders in global scope, but not regionally. Third, leadership in the regional scope provides opportunities for leaders from non-Banu Quraish to assume leadership positions. Fourth, the opportunity to become a leader for non-Banu Quraish must keep in mind the criteria or conditions for being a leader. Starting from who chooses then who will be chosen.